A personal reflection of the impact of adopting a student-centred teaching approach to influence accounting students’ approaches to learning - Wilmot, Lanelle Jean; Merino, Andres (South African Journal of Higher Education, 2016)
This study explores how both my teaching practice and students’ learning approaches evolved as I embarked on a project to help students take responsibility for their own learning and acquire specific self-regulated learning (SRL) skills. The intervention involved ten tutorials taught to a pilot group of twenty eight students studying Financial Accounting in a South African School of Accountancy. During the intervention I made use of guided mastery principles and student-centred activities to teach learning strategies and skills. Action research was used as a tool to assist in designing the intervention, reflecting on and then evaluating the findings. Qualitative data was collected in the form of written and verbal feedback from group participants, colleagues, and through use of a research diary. The findings indicate that guided mastery and active learning are effective techniques for teaching specific SRL skills to students. The feedback provided by students also shows that the intervention fostered student learning. My own teaching practice also improved through reflecting on and making changes to my teaching approach. Keywords Self-regulated learning, reflective practice, accountancy education, student-centred learning, guided mastery.